2017
DOI: 10.1080/09513590.2017.1412429
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian response to controlled ovarian stimulation in women with different polycystic ovary syndrome phenotypes

Abstract: Controlled ovarian stimulation (COH) in PCOS is a challenge for fertility expert both ovarian hyperstimulation syndrome (OHSS) and oocytes immaturity are the two major complication. Ovarian response to COH vary widely among POCS patients and while some patients are more likely to show resistance to COH, other experienced an exaggerated response. The aim of our study is to investigate a possible correlation between PCOS phenotypes and the variety of ovarian response to COH and ART outcomes in patients with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
4
21
0
1
Order By: Relevance
“…Firstly, we did not nd any differences in the woman's BMI between the three A, C and D phenotypes -as also reported in a recent case-control study [39]. Secondly, the PCOS phenotype A population exhibited the highest AMH levels, which is in line with previous reports [18,19,39,40]. Furthermore, the severity of OA appeared to be correlated with an elevated serum AMH level [41,42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Firstly, we did not nd any differences in the woman's BMI between the three A, C and D phenotypes -as also reported in a recent case-control study [39]. Secondly, the PCOS phenotype A population exhibited the highest AMH levels, which is in line with previous reports [18,19,39,40]. Furthermore, the severity of OA appeared to be correlated with an elevated serum AMH level [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, it is well known that oocyte competence in uences embryonic development [15]. To date, only a few studies have assessed the potential impact of different PCOS phenotypes on the outcomes of assisted reproductive technologies [16][17][18][19]. In a study of IVF procedures, Ramezanali and colleagues (2016) reported lower clinical pregnancy rates in PCOS phenotypes A and B than in controls -suggesting that the combination of HA and OA may affect embryonic development [18].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are similar to those in a previous study (92% specificity and 79% sensitivity) [35]. Serum AMH levels in another recent study added values in classifying different PCOS phenotypes that might help clinicians identify patients at high risk of ovarian hyperstimulation syndrome and customize specific therapies [36].…”
Section: Discussionsupporting
confidence: 89%
“…The current study appeared increased result of AMH in (55.0%) of PCOS patients more than normal value. This study agreed with recent Iraqi study finished by (Mohaisen et al,2019) (18) in Misan city.Several recent studies confirmed by (Deshmukh et al,2019) (19) in England and by (Cela. et al,2018) (20) in Italy,that reported increased AMH level in PCOS ladies than healthy ladies.The increase level of serum AMH in PCOS refer to the fact that AMH level indicate the count of small antral follicles and increased secretion of AMH per follicle and therefore the increased AMH expression has been indicated in the phase of preantral and small antral follicle size (4-8mm) and dissolve in follicle size more than 9 mm (21) .…”
Section: Resultsmentioning
confidence: 72%